Evaluation of deformation and strength parameters of organic soils for the design of geotechnical structures - Zbigniew Lechowicz; Katarzyna Goławska (Acta Polytechnica CTU Proceedings, 2023)
The evaluation of deformation and strength parameters of Holocene organic soils obtained from DMT dilatometer tests based on empirical relationships and ANN Artificial Neural Networks is presented. The evaluation of undrained shear strength τfu, deformation modulus E0.1% and initial shear modulus G0 of Eemian organic soils obtained from DMT dilatometer tests and SDMT seismic dilatometer tests is given, and then its comparison with the values obtained from triaxial tests for the design of underground structures supported by diaphragm walls of the stations of the underground line II in Warsaw, is shown.